Analisis Ekonomi Politik Media Dalam Pemasaran Politik Paslon Capres-Cawapres Pemilu 2024 - Dewi, Liza Dwi Ratna; Rusadi, Udi (Avant Garde, 2024)
The 2024 General Election in Indonesia was held on Wednesday 14 February 2024, which included selecting presidential and vice presidential candidates for the 2024-2029 period. On March 20 2024, the General Election Commission has determined the winner of serial number 02 Prabowo Subianto – Gibran Rakabuming Raka. This research is a study of the political economy of the media with the case of the general election. The theories and concepts used are Eric Louw's theory of meaning formation, Moscow spatialization-structuration-commodification, and Kotler Armstrong's political marketing. The paradigm used is interpretive-critical with cultural andpolitical  marketing approaches, and ethnographic methods. The research subjects are 5 categories of voters in the 2024 election, and the research object is the cultural pattern of media consumption related to political information in the 2024 election. Data collection techniques using interviews, observation, internet and literature study. This research shows 3 findings, namely: The political power of media has moved from television media, which has been categorized as the main media for disseminating political information, to social media managed by influencers who are Indonesian artists and celebrities; Digital media can be used to attract voters instantly, but it destroys social dialogue in public spaces in cyberspace. Political information on social media contains artificial information in the sense of information that is not related to politics and democracy, but determines people's choices in selecting candidates for president and vice president of Indonesia for the 2024-2029 period. This research offers a novelty concept, namely artificial political information.